2000
DOI: 10.1128/jb.182.24.7092-7096.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Truncated Form of the Bacterial Heat Shock Protein ClpB/HSP100 Contributes to Development of Thermotolerance in the Cyanobacterium Synechococcus sp. Strain PCC 7942

Abstract: ClpB is a highly conserved heat shock protein that is essential for thermotolerance in bacteria and eukaryotes. One distinctive feature of all bacterial clpB genes is the dual translation of a truncated 79-kDa form (ClpB-79) in addition to the full-length 93-kDa protein (ClpB-93). To investigate the currently unknown function of ClpB-79, we have examined the ability of the two different-sized ClpB homologues from the cyanobacterium Synechococcus sp. strain PCC 7942 to confer thermotolerance. We show that the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…Proteolytic removal of the C terminus in V813M supports the requirement of this domain for function, which as stated before, may involve not only hexamerization, but also effector binding (Smith et al, 1999;Strub et al, 2003). Although our screen was not performed to saturation, it is notable that no loss-of-function suppressors were obtained in the N-terminal domain, which has also not been associated with an essential function in other organisms (Clarke and Eriksson, 2000;Beinker et al, 2002;Mogk et al, 2003b).…”
Section: Online)supporting
confidence: 72%
See 2 more Smart Citations
“…Proteolytic removal of the C terminus in V813M supports the requirement of this domain for function, which as stated before, may involve not only hexamerization, but also effector binding (Smith et al, 1999;Strub et al, 2003). Although our screen was not performed to saturation, it is notable that no loss-of-function suppressors were obtained in the N-terminal domain, which has also not been associated with an essential function in other organisms (Clarke and Eriksson, 2000;Beinker et al, 2002;Mogk et al, 2003b).…”
Section: Online)supporting
confidence: 72%
“…Biochemical studies using both in vitro assays for ATP hydrolysis and protein disaggregation (chaperone activity), along with in vivo assays for thermotolerance, have also begun to dissect functional domains of Hsp100/ClpB (Smith et al, 1999;Barnett et al, 2000;Clarke and Eriksson, 2000;Schirmer et al, 2001;Beinker et al, 2002;Cashikar et al, 2002;Mogk et al, 2003b;Strub et al, 2003). However, details of the Hsp100/ClpB reaction cycle are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). The NTD was shown to be dispensable for chaperone activity in Escherichia coli and Thermus thermophilus (Beinker et al, 2002;Mogk et al, 2003) and for thermotolerance in cyanobacteria and yeast (Clarke and Eriksson, 2000;Hung and Masison, 2006). However, work on E. coli ClpB showed that truncation of the NTD causes severe defects in molecular chaperone activity in vitro (Barnett et al, 2000;Li and Sha, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These truncated proteins function well in protein disaggregation and the role of the NTD in ClpB function is still speculative (Clarke and Eriksson 2000;Beinker et al 2002;Mogk et al 2003;Chow et al 2005). The NTD of ClpB can affect interactions with aggregated model substrates (Beinker et al 2002;Tek and Zolkiewski 2002;Mogk et al 2003;Barnett et al 2005), but this activity clearly is not essential for ClpB to recognize and act on protein aggregates.…”
Section: H25ymentioning
confidence: 99%